2018
DOI: 10.1080/09599916.2018.1457070
|View full text |Cite
|
Sign up to set email alerts
|

The implied internal rate of return in conventional residual valuations of development sites

Abstract: Explicit discounted cash flow methods are used in many countries to assess the value of property investments or their likely rate of return given a particular price. These are typically supplemented by simpler models for the purpose of estimating market value and this has led to debate over the merits of different approaches. A parallel situation exists in the case of UK development sites: both cash flow appraisals and simpler residual valuations are used by the real estate industry to assess site values and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 11 publications
1
18
0
Order By: Relevance
“…Larger commercial developers, using cash flow appraisals and developing longer schemes, quoted per annum IRR targets of around 10-12%; this reconciles with requiring higher cash returns for longer projects. Crosby et al (2018) found that IRRs and profit-on-cost were similar in magnitude for projects around two years in length, with shorter projects producing higher IRRs and longer projects producing lower IRRs from a static profit-on-cost target. There was comment in the interviews about target returns increasing for longer projects and this would seem logical for cash metrics in order to maintain a constant IRR.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Larger commercial developers, using cash flow appraisals and developing longer schemes, quoted per annum IRR targets of around 10-12%; this reconciles with requiring higher cash returns for longer projects. Crosby et al (2018) found that IRRs and profit-on-cost were similar in magnitude for projects around two years in length, with shorter projects producing higher IRRs and longer projects producing lower IRRs from a static profit-on-cost target. There was comment in the interviews about target returns increasing for longer projects and this would seem logical for cash metrics in order to maintain a constant IRR.…”
Section: Discussionmentioning
confidence: 92%
“…Figure 8 shows that, for development length, respondents were equally divided between increasing the profit target for longer developments or not adjusting it at all. One explanation for this finding could be that those developers using cash flow techniques keep the target rate static because it allows already for the time effect, while those using conventional residual techniques need to raise their profit target to maintain a similar periodic return rate (see Crosby et al, 2018). However, crosstabulation of the responses showed that this was not the case; there was no significant difference in answers when responses were categorised in this way.…”
Section: Insert Table 2 Herementioning
confidence: 99%
See 3 more Smart Citations